Sistem Pendukung Keputusan Untuk Menentukan Kelayakan Penerima Beasiswa Yayasan Dengan Metode AHP Berbasis Dynamic Website Engineering - Aidatul Amelia; Roberto Kaban; Asprina Br. Surbakti (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
The Analytical Hierarchy Process (AHP) method was chosen because it is able to select the best alternative. The research was carried out by finding the weight value for each attribute, then a candidate sorting process was carried out which would determine the optimal alternative, namely the most worthy candidate for scholarship recipients. In creating a Decision Support System for selection of prospective scholarship recipients, the author used the PHP and MySQL programming language as a database. From this research process, a Dynamic Website Engineering was produced, namely a decision support system for the selection of prospective scholarship recipients at STIT Al-Washliyah Binjai which not only can be used with criteria and alternatives at the beginning of the design, but can also be added or deleted at any time if there are changes. high school policy.